2012
DOI: 10.1073/pnas.1204787109
|View full text |Cite
|
Sign up to set email alerts
|

Eilat virus, a unique alphavirus with host range restricted to insects by RNA replication

Abstract: Most alphaviruses and many other arboviruses are mosquito-borne and exhibit a broad host range, infecting many different vertebrates including birds, rodents, equids, humans, and nonhuman primates. Consequently, they can be propagated in most vertebrate and insect cell cultures. This ability of arboviruses to infect arthropods and vertebrates is usually essential for their maintenance in nature. However, several flaviviruses have recently been described that infect mosquitoes but not vertebrates, although the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
191
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 171 publications
(201 citation statements)
references
References 41 publications
10
191
0
Order By: Relevance
“…To extend our previous findings, viral factors responsible for EILV host range restriction at the genomic RNA replication level were investigated (28). The lack of reporter expression following electroporation of synthetically capped EILV genomes suggested a potential role for the 3= UTR, which is critical to alphavirus RNA replication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To extend our previous findings, viral factors responsible for EILV host range restriction at the genomic RNA replication level were investigated (28). The lack of reporter expression following electroporation of synthetically capped EILV genomes suggested a potential role for the 3= UTR, which is critical to alphavirus RNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…This raises the intriguing possibility that EILV descended from a member of the WEE complex that lost the ability to infect vertebrates as the virus adapted unilaterally to its mosquito host. Several lines of evidence support this hypothesis: (i) antigenic cross-reactivity of EILV with members of WEE complex, SINV, WEEV, and Aura virus (AURAV); (ii) the phylogenetic placement based on the nsP ORF groups EILV within the WEE complex, basal to Whataroa virus (WHATV); and (iii) EILV nsPs and sPs display greater amino acid identity to SINV, WHATV, and AURAV than to other mosquito-borne viruses: nsP1 (71 to 73%), nsP2 (60 to 65%), nsP4 (74 to 77%), capsid (50 to 53%), E1 (49% to 50%), and E2 (40% to 42%) (28). The proposed hypothesis provides an interesting interpretation of these results (28).…”
Section: Fig 8 Predicted Secondary Structure Of Eilv (A) and Sinv (B) 3=mentioning
confidence: 99%
See 1 more Smart Citation
“…This group of viruses is very diverse, representing many different virus families and genera (Togaviridae, Flaviviridae, Bunyaviridae, Rhabdoviridae, Reoviridae, Mesoniviridae, Negevirus) and other still unclassified RNA viruses. [9][10][11][12]14,45,46 Data are lacking on the basic ecology of most insect-specific viruses in nature and their potential effects on mosquito life-history traits and the arboviruses they transmit. When conducting vector competence experiments, investigators should consider screening laboratory mosquito colonies for persistent insectspecific viral infections, and endosymbiotic bacteria, to be aware of potential variables that could alter resulting data sets.…”
Section: Discussionmentioning
confidence: 99%
“…1 Recent studies have shown that the microbiota of mosquitoes can affect their ability to become infected with and to vector certain pathogens. [2][3][4][5] There is a growing realization that mosquito populations are naturally infected with a wide range of bacteria, 6,7 fungi, 8 and viruses [9][10][11][12][13][14][15] ; and this recognition has raised interest in the potential effects of these microbes on mosquito ecology and on pathogen transmission.…”
Section: Introductionmentioning
confidence: 99%